2012
DOI: 10.3892/etm.2012.833
|View full text |Cite
|
Sign up to set email alerts
|

Posterior decompression and short segmental pedicle screw fixation combined with vertebroplasty for Kümmell’s disease with neurological deficits

Abstract: The aim of this study was to investigate the treatment of Kümmell’s disease with neurological deficits and to determine whether intravertebral clefts are a pathognomonic sign of Kümmell’s disease. A total of 17 patients who had initially been diagnosed with Kümmell’s disease were admitted, one patient was excluded from this study. Posterior decompression and vertebroplasty for the affected vertebrae were conducted. Pedicle screw fixation and posterolateral bone grafts were performed one level above and one lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 20 publications
2
56
1
Order By: Relevance
“…To the best of our knowledge, no current literature reports compare these two surgical methods. Although both groups achieved similar short-term clinical outcomes, including pain relief, vertebral height recovery, and malformation improvement (P > 0.05), the long-term effects were different; the PFVP group had significant losses of AVH and LKA progression during the 2year follow-up compared to the PVCR group (P < 0.05), which is different from previous studies [20,[33][34][35]. As kyphosis was aggravated over time, patients in the PFVP group complained of more severe back pain than those in the PVCR group (P < 0.05), which is consistent with the VAS results observed in our study.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…To the best of our knowledge, no current literature reports compare these two surgical methods. Although both groups achieved similar short-term clinical outcomes, including pain relief, vertebral height recovery, and malformation improvement (P > 0.05), the long-term effects were different; the PFVP group had significant losses of AVH and LKA progression during the 2year follow-up compared to the PVCR group (P < 0.05), which is different from previous studies [20,[33][34][35]. As kyphosis was aggravated over time, patients in the PFVP group complained of more severe back pain than those in the PVCR group (P < 0.05), which is consistent with the VAS results observed in our study.…”
Section: Discussioncontrasting
confidence: 85%
“…However, this method requires relatively high-level surgical skills and a long learning curve [25]. us, for this condition, some scholars have recently recommended PFVP, a relatively simple and minimally invasive approach that does not need to address the anterior lesion [20,26]. Lee et al [26] showed that PFVP is an effective treatment for OVCFs with IVC complicated by neurologic symptoms; however, the authors observed an average 4.5°loss of correction in the kyphotic angle at the final follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditional surgical interventions may be the first treatment choice for a majority of patients, as conservative treatments, including analgesics and bed rest, exhibit little benefit in pain relief (8). However, shortcomings of open surgery, including major trauma and long recovery times are concerns for patients (9).…”
Section: Introductionmentioning
confidence: 99%